2020
DOI: 10.1021/acschembio.0c00446
|View full text |Cite
|
Sign up to set email alerts
|

Pentavalent Sialic Acid Conjugates Block Coxsackievirus A24 Variant and Human Adenovirus Type 37–Viruses That Cause Highly Contagious Eye Infections

Abstract: Coxsackievirus A24 variant (CVA24v) and human adenovirus 37 (HAdV-37) are leading causative agents of the severe and highly contagious ocular infections acute hemorrhagic conjunctivitis and epidemic keratoconjunctivitis, respectively. Currently, neither vaccines nor antiviral agents are available for treating these diseases, which affect millions of individuals worldwide. CVA24v and HAdV-37 utilize sialic acid as attachment receptors facilitating entry into host cells. Previously, we and others have shown that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 41 publications
(138 reference statements)
3
40
0
Order By: Relevance
“…In an ongoing research project, we were interested in studying the potential of 4-O-alkyl analogs of 5 (Figure 1) as probes targeting cell attachment during adenovirus [31][32][33] and coxsackievirus infections 34,35 .…”
Section: Resultsmentioning
confidence: 99%
“…In an ongoing research project, we were interested in studying the potential of 4-O-alkyl analogs of 5 (Figure 1) as probes targeting cell attachment during adenovirus [31][32][33] and coxsackievirus infections 34,35 .…”
Section: Resultsmentioning
confidence: 99%
“…These studies used the same SV40 immortalized corneal epithelial cell line [ 48 ] discussed above. Subsequent work showed that some but not all of the EKC-associated HAdVs bind to sialic acid-expressing cell surface glycans [ 85 ], and that various multivalent sialic acid constructs could block binding [ 84 , 86 , 87 , 88 , 89 , 90 , 91 ]. Sites on the fiber knob that bind to the various potential adenovirus receptors have been mapped in exquisitely detailed structural studies [ 92 ].…”
Section: Corneal Epithelial Cell Tropism and Receptorsmentioning
confidence: 99%
“…Binding and infection experiments using corneal cells indicate that the cell surface receptor used by CVA24v is composed of a sialylated disaccharide (Neu5Acα2,3Gal) on O-glycosylated proteins ( 29 ). Consequently, derivatives based on sialic acid have been developed and shown to be effective in preventing HAdV-D37 and CVA24v binding and infection of human corneal epithelial cells ( 30 , 31 ).…”
Section: The Glycocalyx In Ocular Surface Infectionmentioning
confidence: 99%